Preliminary research on field measurement of spectral emissivity of rice in thermal infrared - LIN Fen-fang; DENG Jing-song; DING Xiao-dong; AO Wei-jiu; WANG Ke (浙江大学学报. 农业与生命科学版)
The procedure and method of emissivity field measurement for rice were conducted using a portable Fourier transform infrared spectrometer. The results showed that rice emissivity value measured indoor was very close to 1.0, and no distinct emissivity characteristics were found in the spectral curves. Consequently, the field measurement should be carried out under generally clear sky conditions and low to moderate relative humidity, and the distance between the instrument and the objective should be shortened in order to make leaves fully within the instrument field of view. Moreover, in terms of the processing methods, the iterative spectrally smooth algorithm instead of the Planck function was the suitable method to remove atmospheric features and extract the surface spectral emissivity of plants.